Mercy as benchmark of social relationship : a reflection - Abdullah, Fatimah (International Islamic University Malaysia, 2011)
Allah is All-Merciful and Oft-Forgiving. When Allah breathed into man His own Spirit, He indeed transferred into his nature essence of some of His attributes, including mercy and forgiveness. Islam teaches its followers to be merciful and forgiving to others. This Islamic teaching forms the basis of social relationship among believers and also non-believers. The social relationship based on, among others, the principle of mercy leads not only to the pleasure of Allah and to the paradise in the hereafter but also brings about a total change in human life on the earth, creating an environment replete with peace, love, trust, and development. This article tries to highlight the role of mercy in human life.